2017
DOI: 10.1021/acsami.7b01709
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional CH3NH3PbI3 Perovskite Nanosheets for Ultrafast Pulsed Fiber Lasers

Abstract: Even though the nonlinear optical effects of solution processed organic-inorganic perovskite films have been studied, the nonlinear optical properties in two-dimensional (2D) perovskites, especially their applications for ultrafast photonics, are largely unexplored. In comparison to bulk perovskite films, 2D perovskite nanosheets with small thicknesses of a few unit cells are more suitable for investigating the intrinsic nonlinear optical properties because bulk recombination of photocarriers and the nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
183
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(196 citation statements)
references
References 33 publications
2
183
1
Order By: Relevance
“…Compared to its bulk counterparts and thin NCs films, 2D metal‐halide perovskites are more suitable for investigating intrinsic nonlinear optical properties for its relatively small photocarriers recombination and nonlinear scattering . The nonlinear absorption coefficient of 2D perovskite nanosheet is two orders of magnitude larger than that of the bulk perovskite, and 2D perovskite is able to achieve mode locking at lower power threshold than bulk one, as shown in Figure d.…”
Section: Photonics Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to its bulk counterparts and thin NCs films, 2D metal‐halide perovskites are more suitable for investigating intrinsic nonlinear optical properties for its relatively small photocarriers recombination and nonlinear scattering . The nonlinear absorption coefficient of 2D perovskite nanosheet is two orders of magnitude larger than that of the bulk perovskite, and 2D perovskite is able to achieve mode locking at lower power threshold than bulk one, as shown in Figure d.…”
Section: Photonics Applicationsmentioning
confidence: 99%
“…and comparable to few‐layers graphene . By transferring suitable 2D perovskite nanosheets onto the end facet of an optical fibre ferrule to fabricate a saturable absorber, a ultrafast picosecond pulses can be generated, as shown in Figure e. However, the nonlinear property such as second harmonic generation (SHG) has been rarely reported in emerging perovskite with form AMX 3 .…”
Section: Photonics Applicationsmentioning
confidence: 99%
“…Today, all‐inorganic perovskite materials are widely used in photovoltaic devices, such as solar cells, photodetectors, and light‐emitting diodes. All‐inorganic perovskite materials with different morphologies have their own advantages in application, and nanoplates have excellent light absorption coefficients, good electrical transmission capacities, and high environmental stabilities; thus, these materials hold potential for preparing optoelectronic synapses in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 2D perovskites have attracted increasing research interest and been applied to diverse fields, such as light‐emitting diodes (LEDs), solar cells, and PDs, because of the advantages peculiar to them . First, inherited from their bulk counterparts and originated from their reduced dimension, 2D perovskites exhibit a variety of intriguing properties, including tunable bandgap, high photoconductive gain, high photoluminescence (PL) efficiency, and nonlinear optical properties . Second, it is found that many properties of 2D perovskites are strongly dependent on their thickness, and the properties show increased sensitivity to applied external fields owing to their ultrathin thickness .…”
mentioning
confidence: 99%